Formal Logic, Representation and Intuition: The limits of classical representation and intuition of abstract objects - Fernández Cuesta, José Alejandro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The Philosophical study of the representation of mathematical objects requires a prior definition of what we mean by intuition. In this article I introduce an argument that shows why we cannot represent every conceptually manipulable object. To reach this conclusion I will admit that there are certain abstract objects that cannot be apprehended intuitively. In order to do so, I will historically review their characterisation and formal definition. Finally, I will establish an updated basis on which to initiate a specific study of the role of object representation in formal science.